Efforts to Increase Student Learning Motivation Through Audio Visual Media in Islamic Religious Education Subjects at SMAN 06 Prabumulih - Noprianah, Nisa (Rumah Riset Publisher, 2023)
This research begins with a problem that is the learning process of Islamic of Education (PAI) in SMAN 6 Prabumulih still often use speech method and simple instructional media, not yet maximize the use of interactive learning media interesting, while media of Audio Visual learning is rarely applied to the learning process PAI lessons so that the learning process does not work effectively. This study aims to describe of increased student learning motivation in the subjects of PAI by using audiovisual media. This research uses classroom action research method consisting of four stages namely, planning, action, observation, and reflection. Data collection in this research through observation, interview, and documentation. This study lasted for two cycles. The data analysis used is with the relative frequency distribution. The results of research by using audiovisual media can improve students' learning motivation in the subjects of PAI class XI IPS in SMA Negeri 06 Prabumulih. In the first cycle, student learning motivation reached 83.33%. In the second cycle, student learning motivation increased 10% to reach 93.33% so the study was stopped in cycle II. Thus, the use of audio-visual media can improve students' learning motivation on the subjects of Islamic Religious Education (PAI) class XI IPS in SMA Negeri 06 Prabumulih.